Optimalisasi Zakat Produktif dalam Mendorong Pertumbuhan Ekonomi UMKM Berbasis Syariah di Indonesia - Maharati, Cindy (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2024)
This study aims to examine the strategic role of productive zakat in promoting the growth of sharia-based micro, small, and medium enterprises (MSMEs) in Indonesia. Employing a qualitative-conceptual approach through an extensive literature review, the research offers a theoretical and empirical synthesis of the contributions of productive zakat across three economic levels: micro, meso, and macro. The findings reveal that productive zakat not only increases income and economic self-reliance among beneficiaries (mustahik) but also strengthens local Islamic economic ecosystems and supports national poverty reduction efforts. These contributions position zakat as a transformative and sustainable socio-economic instrument. However, the optimization of productive zakat faces structural challenges, including weak institutional integration, low Islamic financial literacy, and underdeveloped regulatory frameworks. Therefore, institutional transformation is necessary through empowerment-oriented fiscal policies, digitalized beneficiary data systems, and alignment of zakat programs with the national roadmap for sharia-based MSME development. Overall, the study confirms that productive zakat holds great potential as a foundational pillar for an inclusive, just, and sustainable Islamic economic system.